Role of Histone Methyltransferase G9a in CpG Methylation of the Prader-Willi Syndrome Imprinting Center - Xin, Zhenghan; Tachibana, Makoto; Guggiari, Michele; Heard, Edith; Shinkai, Yoichi; Wagstaff, Joseph (The Journal of biological chemistry, 2003)
Imprinted genes in mammals are often located in clusters whose imprinting is subject to long range regulation by cis-acting sequences known as imprinting centers (ICs). The mechanisms by which these ICs exert their effects is unknown. The Prader-Willi syndrome IC (PWS-IC) on human chromosome 15 and mouse chromosome 7 regulates imprinted gene expression bidirectionally within an ∼2-megabase region and shows CpG methylation and histone H3 Lys-9 methylation in somatic cells specific for the maternal chromosome. Here we show that histone H3 Lys-9 methylation of the PWS-IC is reduced in mouse embryonic stem (ES) cells lacking the G9a histone H3 Lys-9/Lys-27 methyltransferase and that maintenance of CpG methylation of the PWS-IC in mouse ES cells requires the function of G9a. We show by RNA fluorescence in situ hybridization (FISH) that expression of Snrpn, an imprinted gene regulated by the PWS-IC, is biallelic in G9a −/− ES cells, indicating loss of imprinting. By contrast, Dnmt1 −/− ES cells lack CpG methylation of the PWS-IC but have normal levels of H3 Lys-9 methylation of the PWS-IC and show normal monoallelic Snrpnexpression. Our results demonstrate a role for histone methylation in the maintenance of parent-specific CpG methylation of imprinting regulatory regions and suggest a possible role of histone methylation in establishment of these CpG methylation patterns.